Manufacturing Revolution Boosts People Issues: The Evolutionary Need for `Human-Automation Resource Management' in Smart Factories - Volker Stein; Tobias M. Scholz (European Management Review, 2019)
Driven by significant innovations in manufacturing on the edge of a `second machine age', automation will play a pivotal role in turning the world of work upside down. Digitized manufacturing is fundamentally changing relations between human and machine. The expected symbiosis has not yet been systematically organized, since human resource management has widely ignored the topic of automation. If HRM fails to answer the final call, it will lose its influence in smart factories, ultimately being replaced by other functions. Our theoretically derived concept of human-automation resource management (HARM) discloses a possible way out by specifically tackling the conjunction between humans and machines. We will sketch HARM as the combination of HRM and automation management and, therefore, as the next evolutionary step in the advancement of HRM. After supporting the strategic integration by means of its synergistic benefits, we will determine the tasks HARM is expected to fulfill at the automation-people-nexus.
Keywords: 650; human resource management; automation; future of industrial labor; manufacturing; smart companies